Determinants Of Repurchase Intention Of Muslim Fashion Products On The Shopee Marketplace Among Generation Z - Wirda, Nurul; Umuri, Khairil; Farma, Junia; Muftahuddin; Najla (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This study aims to analyze the effect of product quality, prices, shopping experience, and trust on repurchase interest in Muslim fashion products in the Shopee marketplace. The study utilized primary data, with a quantitative approach, and Generation Z in Banda Aceh City as the population. The sample size consisted of 115 respondents, selected using non-probability and purposive sampling methods. The data were analyzed using multiple linear regression with SPSS. The research finding indicate that the price variable had a notable effect on repurchase interest, while the variables of product quality, shopping experience, and trust did not affect repurchase interest. Meanwhile, the variables of product quality, prices, shopping experience, and trust affect repurchase interest simultaneously. In accordance with those findings, the sellers are supposed to prioritize competitive pricing strategies to increase repurchase interest. The merchants are suggested to improve product quality and build consumer trust to increase customer loyalty. Future researchers can probe into the role of each variable in the context of different products and platforms.